(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It traces the trajectory of climate conferences from Stockholm to Dubai, highlighting legal and political advancements. It contextualizes COP-30 as a strategic step that symbolizes the Amazon’s leading role and Brazil’s leadership in climate cooperation. (Received: September 2025 | Accepted: November 2025)